Komunikasi Dalam Pengembangan Hubungan Antarpribadi Melalui Second Account Instagram - Herna Herna; Annisa Alifya Sari (WACANA: Jurnal Ilmiah Ilmu Komunikasi, 2023)
Human beings have a need to express themselves and define their identity. With the existence of a second account on Instagram, individuals can express aspects that may not be fully revealed on the main account. The study aims to understand communication in the development of interpersonal relationships in users and followers of second Instagram accounts.  The method used is qualitative descriptive research with a constructivism research paradigm. The theory used is Social Penetration Theory which explains the development of interpersonal relationships that include depth and breadth in interaction.  The results showed that the younger generation, especially students, use Instagram second accounts to form relational partners through relationship development.  Relationship development is done by means of self-disclosure, both in terms of depth and breadth and establishing presence over time.  Each user's distinct personality determines the level of self-disclosure. Communication moves from the exploratory stage to a more intimate relationship depending on whether the relationship produces positive benefits.  If the user feels the benefits, then the information shared will show intimacy (mutual understanding and support), conversely, if the user does not feel the benefit or satisfaction of the relationship with someone who is his follower, then the user will hide the followers from the close friends feature or unfriend in the second account.